The Effect of Neutrophil Lymphocyte Ratio and Bacterial Co-Infection on Mortality and Length of Hospital Stay of COVID-19 Patients - Renata, Felicia; Adhiputri, Artrien; Suyatmi, Suyatmi (Universitas Muhammadiyah Semarang, 2024)
Background: The new coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly contagious disease. The disease has spread rapidly and widely around the world, and was declared as pandemic in March 2020 by WHO. The neutrophil lymphocyte ratio (NLR) is a biomarker that provides important information about the status of systemic inflammation, including in COVID-19. Bacterial co-infection is commonly identified in viral respiratory tract infections such as SARS-CoV-2 and is an important cause of morbidity and mortality.Objective: This study aims to retrospectively analyze clinical data of COVID-19 patients who were treated at Dr. Moewardi General Hospital in Surakarta, to determine the effect of NLR and bacterial co-infection with mortality and length of hospital stay of COVID-19 patients.Methods: This study is an analytical observational study with a cross-sectional design using secondary data from 87 adult COVID-19 patients at Dr. Moewardi Hospital in August 2021. The sampling method used was purposive sampling of all adult patients aged 18 years or above who had been diagnosed with COVID-19 and hospitalized.Results: It was found that there was a strong effect of bacterial co-infection on NLR (r= 0.528). It was also found that NLR and bacterial co-infection simultaneously affected the length of hospital stay (Sig.= 0.02) and mortality (Sig.= 0.027). Partially, the effect of NLR on length of hospital stay was found (Sig.= 0.045).Conclusion: NLR and bacterial co-infection have an effect on mortality and length of hospital stay of COVID-19 patients.